Rapid Microbial Dynamics in Response to an Induced Wetting Event in Antarctic Dry Valley Soils - Niederberger, Thomas D.; Bottos, Eric M.; Sohm, Jill A.; Gunderson, Troy; Parker, Alex; Coyne, Kathryn J.; Capone, Douglas G.; Carpenter, Edward J.; Cary, Stephen Craig (Frontiers in Microbiology, 2019)
The cold deserts of the McMurdo Dry Valleys (MDV), Antarctica, host a high level of microbial diversity. Microbial composition and biomass in arid vs. ephemerally wetted regions are distinctly different, with wetted communities representing hot spots of microbial activity that are important zones for biogeochemical cycling. While climatic change is likely to cause wetting in areas not historically subject to wetting events, the responses of microorganisms inhabiting arid soils to water addition is unknown. The purpose of this study was to observe how an associated, yet non-wetted microbial community responds to an extended addition of water. Water from a stream was diverted to an adjacent area of arid soil with changes in microbial composition and activities monitored via molecular and biochemical methods over seven weeks. The frequency of genetic signatures related to both prokaryotic and eukaryotic organisms adapted to MDV aquatic conditions increased during the limited seven week period, indicating that the soil community was transitioning into a typical “high-productivity” MDV community. This work is consistent with current predictions that MDV microbial communities in arid regions are highly sensitive to climate change, and further supports the notion that changes in community structure and associated biochemical cycling may occur much more rapidly than predicted.